2021
DOI: 10.1186/s40352-021-00142-w
|View full text |Cite
|
Sign up to set email alerts
|

Family member incarceration and coping strategies during the COVID-19 pandemic

Abstract: Background The disproportionately high rate of incarceration and COVID-19 cases during the summer of 2020 in the United States contributed to a set of circumstances that has produced considerable public health concerns as correctional facilities have emerged as significant COVID-19 hot spots. During the COVID-19 pandemic, having a family member incarcerated can be an especially stressful experience. This study assesses how concern about an incarcerated family member contracting COVID-19 impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…For example, throughout the pandemic, harrowing reports of illness and death inside jails and prisons have made it evident that justice-involved people and communities have also been defined as sacrificial. In the U.S., the COVID infection rate in jails and prisons has been as high as three times greater than the general population (Testa & Fahmy, 2021). As prisons and jails, themselves increasingly privatized, perennially fail in their responsibility to protect the basic health and safety of those under confinement, many of the 2.5 million people incarcerated in U.S. prisons have been unable to see their loved ones in person.…”
Section: Retrenching Reproductive Injustice Through Blatant and Laten...mentioning
confidence: 99%
“…For example, throughout the pandemic, harrowing reports of illness and death inside jails and prisons have made it evident that justice-involved people and communities have also been defined as sacrificial. In the U.S., the COVID infection rate in jails and prisons has been as high as three times greater than the general population (Testa & Fahmy, 2021). As prisons and jails, themselves increasingly privatized, perennially fail in their responsibility to protect the basic health and safety of those under confinement, many of the 2.5 million people incarcerated in U.S. prisons have been unable to see their loved ones in person.…”
Section: Retrenching Reproductive Injustice Through Blatant and Laten...mentioning
confidence: 99%
“…Both COVID-19 and incarceration are serious public health concerns (Testa & Fahmy, 2021), and existing evidence shows disproportionate rates of COVID-19 infection among incarceration-exposed populations (Saloner et al, 2020). The results from the current study detailed that formerly incarcerated individuals were less likely to abide by key COVID-19 mitigation protocols and exposed higher levels of vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…Dallaire and colleagues (2021) concluded that the clarity of the information presented on facilities’ websites was associated with the total number of policy changes made related to other forms of contact with family members. Early research has shown the mental health impacts on families with incarcerated loved ones demonstrating the need to disentangle the role of restrictions on communication (Testa & Fahmy, 2021).…”
Section: Responses and Restrictions During Covid-19mentioning
confidence: 99%